Phytochemical Investigation of Equisetum arvense and Evaluation of Their Anti-Inflammatory Potential in TNFα/INFγ-Stimulated Keratinocytes - Se Yun Jeong; Hyung-Seok Yu; Moon-Jin Ra; Sang-Mi Jung; Jeong-Nam Yu; Jin-Chul Kim; Ki Hyun Kim (MDPI AG, 2023)
Equisetum arvense L. (Equisetaceae), widely known as 'horsetail', is a perennial plant found extensively across Asia. Extracts of E. arvense have been used in traditional medicine, particularly for the treatment of inflammatory disorders. This study aimed to determine the phytochemical compounds in E. arvense ethanolic extract and their anti-inflammatory properties. Subsequently, we isolated and identified nine secondary metabolites, including kaempferol 3,7-di-O-β-D-glucopyranoside (1), icariside B2 (2), (Z)-3-hexenyl β-D-glucopyranoside (3), luteolin 5-O-β-D-glucopyranoside (4), 4-O-β-D-glucopyranosyl caffeic acid (5), clemastanin B (6), 4-O-caffeoylshikimic acid (7), (7S,8S)-threo-7,9,9'-trihydroxy-3,3'-dimethoxy-8-O-4'-neolignan-4-O-β-D-glucopyranoside (8), and 3-O-caffeoylshikimic acid (9). The chemical structures of the isolated compounds (1-9) were elucidated using HR-ESI-MS data, NMR spectra, and ECD data. Next, the anti-inflammatory effects of the isolates were evaluated in tumor necrosis factor (TNF)α/interferon (IFN)γ-induced HaCaT, a human keratinocyte cell line. Among the isolates, compound 3 showed the highest inhibitory effect on the expression of pro-inflammatory chemokines, followed by compounds 6 and 8. Correspondingly, the preceding isolates inhibited TNFα/IFNγ-induced activation of pro-inflammatory transcription factors, signal transducer and activator of transcription 1, and nuclear factor-κB. Collectively, E. arvense could be employed for the development of prophylactic or therapeutic agents for improving dermatitis.